BIM-based facilities information: streamlining the information exchange process. Issue 6 (4th December 2019) - Matarneh, Sandra; Danso-Amoako, Mark; Al-Bizri, Salam; Gaterell, Mark; Matarneh, Rana
Abstract : Purpose: The purpose of this study is to address challenges in the current information exchange process between building information modelling (BIM) and facilities management (FM) systems and to propose a workable solution. This study's objective is to identify the information exchange requirements and to develop methods for seamless information flow between building information models and FM systems. Design/methodology/approach: Data collection and analysis was based on an extensive literature review of similar studies followed by a questionnaire survey with a total of 112 participants and 2 focus groups with a total of 12 participants to validate the conceptual framework. The outputs of the survey analysis formed the background of the proposed framework to streamline information exchange process between building information models and FM systems. Findings: The study findings form a foundation for enabling the integration of various data sources including building information models. Such integrated platforms will enable automated information exchange between the various data sources and FM systems. The study also provides key information requirements sources to complement the existing construction operations building information exchange information and to support standardization for information exchange process. Originality/value: The contribution of this study is the identification of information exchange requirements and sources to enable seamless information flow between BIM and FM systems. The study findings will also lay the basis for research studies using the developed framework context to enable the identification of specific data outputs for FM systems inputs.